Reevaluating the necessity of static shift correction in magnetotelluric inversion - Jingzhong Zeng; Jingzhong Zeng; Xiaobin Chen; Xiaobin Chen; Peijie Wang; Zhongyin Liu; Zhongyin Liu; Juntao Cai; Juntao Cai (Frontiers in Earth Science)
Magnetotelluric (MT) is a significant electromagnetic exploration method. However, due to uneven distribution of surface charges and other factors, static shift often affects observed data, reducing the accuracy of inversion and interpretation. Correcting static shift through data processing remains a challenging task. Based on the characteristic that static shift affects only apparent resistivity data without impacting phase data, this paper proposes an inversion strategy that avoids static shift correction. At sites affected by static shift, apparent resistivity data are excluded, and only phase data are used in the inversion. Synthetic and field data tests indicate that the reduced inclusion of apparent resistivity data has minimal impact on inversion results, and due to the exclusion of data influenced by static shift, the inversion accurately reflects deep anomalous structures. This demonstrates that by excluding apparent resistivity data and relying solely on phase data at static-shifted sites, accurate inversion results can be achieved without additional static shift correction.